An ecosystem services value assessment of land-use change in Chengdu: Based on a modification of scarcity factor. (April 2019) - Kang, Yu; Cheng, Chuanxing; Liu, Xianghua; Zhang, Fan; Li, Zhihui; Lu, Siqi
Abstract: Changes in land-use, caused by rapid urbanization, lead to changes in the supply and demand for ecosystem services. Significant research has been conducted to investigate the impact of changes in the physical supply of ecosystem services on their value. However, quantifying the effects of simultaneous changes in supply and demand on the scarcity value of ecosystem services can provides a more reasonable assessment of ecosystem services, guiding their sustainable use. Therefore, this paper analyzed the changing trend of ecosystem services value in Chengdu in southwestern China from 1995 to 2015 by adjusting the value coefficients with relative changes in scarcity value. Naïve assessment, without considering the supply and demand effect on scarcity value, quantified a decline in the total value of the physical supply of ecosystem services from 1995 to 2015, with a reduction in the areas of cultivated land and woodland. However, the scarcity value of ecosystem services increased from US$ 6.04 billion in 1995 to US$ 12.03 billion (+99.17%) in 2015, when the effects of changes in supply and demand were considered. In addition, the demand for all the public-good ecosystem services increased during the study period, consistenting with Maslow's hierarchy of need and indicating that the demand structure of residents had changed during the process of urbanization. Highlights: The value of physical supply of ecosystem services declines along with the development of urbanization. The scarcity value of ecosystem services has experienced a dramatically increase. People's demand structure has changed with the increasing value of all the public-good ecosystem services. The price elasticity of different ecosystem services is a key factor of scarcity value.